PENERAPAN METODE CRITICAL PATH METHOD (CPM) DAN PROJECT EVALUATION REVIEW TECHNIQUE (PERT) PADA PROYEK PENDIRIAN PESANTREN USIA EMAS DI JONGGOL – KABUPATEN BOGOR - Subarman, Karya; Wijatmoko Hadiprayitno, Weni (INDUSTRIKRISNA, 2025)
The success of a project is very dependent on the planning and control in its implementation. Improper planning and inefficient control will cause delays and increase project costs. Yayasan Cahaya Pena Emas will build a Masjid dan Pesantren Usia Emas located in Jonggol, Bogor Regency with funding from the community in the form of endowments. So that in the implementation of the project there are no problems, especially those related to time or duration, a tool is needed in the form of scheduling for planning and controlling. In this research, the Critical Path Method (CPM) and Project Evaluation Review Technique (PERT) methods will be used. With this method, the Yayasan Cahaya Pena Emas can be assisted in determining critical activities and determining the estimated time to complete the project. From the research results of the two methods, the CPM and PERT methods obtained the critical path on activities A - B - C - D - E - F and N and the duration obtained by the CPM method obtained results of 32 months, while the PERT method obtained the completion duration 33.83 months. It is hoped that the results of this reserach can be used as a guide in project management and it can be known when the pesantren usia emas can start operating.